Public debt and the political economy of reforms - Christoph Esslinger; Pierre Boyer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We consider a model of redistributive politics in which politicians have the possibility to raise some debt and to implement a pie-increasing reform, i.e. a reform creating a net increase in the total taxable endowment. The reform benefits occur in the future and the reform costs have to be paid today, but both benefits and costs can be perfectly redistributed across voters in the period in which they occur. Voters are perfectly forward-looking and ex-ante homogeneous, and politicians are purely office-motivated. As main result, we show that a limit on debt that is sufficiently more restrictive than the natural debt limit will prevent the implementation of the reform. Such a debt limit forces the reforming candidate to pursue an overly egalitarian strategy of redistribution making it possible for a non-reforming candidate to use his better targeting capacity to win a majority of voters.
Keywords: C72; D72; D78; H63; 330